An adaptive constraint handling technique for evolutionary algorithms - Costa, Lino (2010)
In global optimization with evolutionary algorithms, constraint handling presents major difficulties, specially, in the case of equality constraints. Several techniques have been proposed to overcome this difficulty. In this work, an adaptive constraint handling technique is studied on a set of test problems with two evolutionary algorithms. The preliminary results seem to indicate that the proposed adaptive technique produces results with better quality in terms of objective function values and constraint violations.